Sonic and photonic irradiation effects on naphthalene - (:unkn) unknown (My University, 2011)
Solid phase of naphthalene was influenced by sonic (50- 6400Hz) irradiation at room temperature, but the supercooled liquids of naphthalene were independent of applied ultrasonic power. In optical observation, the fractal distribution of microstructures was observed, the sample, which solidified under ultrasonic irradiation without isothermal holding. These results were due to anomalous nucleation caused by the local pressure induced by ultrasonic waves.
Keywords: Attenuation; Fluorescence; Local pressure field; Optical excitation; Sonic and photonic irradiation